2013
DOI: 10.1530/eje-12-1082
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic nervous system balance in children and adolescents with craniopharyngioma and hypothalamic obesity

Abstract: Objective: Dysregulation of the autonomic nervous system is thought to be involved in craniopharyngioma-related hypothalamic obesity (CRHO). Increased parasympathetic activity and decreased sympathetic activity have been suggested. We aimed to study autonomic activity using heart rate variability (HRV) and biochemical measures in youth with CRHO compared with controls and to explore relationships between obesity and autonomic indices. Design: A cross-sectional study of 16 youth with CRHO and 16 controls matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 40 publications
(46 reference statements)
0
22
1
1
Order By: Relevance
“…Hypothalamic obesity is most often caused by an insult to the hypothalamus due to suprasellar tumors or CNS inflammation as in the present case series. In hypothalamic obesity, impairment of hypothalamic function leads to increased parasympathetic activity and decreased sympathetic activity resulting in autonomic instability [17]. …”
Section: Discussionmentioning
confidence: 99%
“…Hypothalamic obesity is most often caused by an insult to the hypothalamus due to suprasellar tumors or CNS inflammation as in the present case series. In hypothalamic obesity, impairment of hypothalamic function leads to increased parasympathetic activity and decreased sympathetic activity resulting in autonomic instability [17]. …”
Section: Discussionmentioning
confidence: 99%
“…[49][50][51][52] In total, 12 studies were considered eligible for the meta-analysis. [53][54][55][56][57][58][59][60][61][62][63][64] Eight studies were included in a meta-analysis comparing CNS tumor survivors self-reported HRQOL to healthy comparisons, including siblings and peers.…”
Section: Objective 1: Summary Of Studiesmentioning
confidence: 99%
“…Studies that analyze the autonomic activity in children investigate changes in the indices of low frequency (LF) and high frequency (HF) as a reflection of the balance of the autonomic nervous system. The increased LF/HF ratio is a factor present in obese children 16,21 .…”
Section: Discussionmentioning
confidence: 99%